Modeling the Incubation Effect Among Students Playing an Educational Game for Physics - Talandron-Felipe, May Marie (Archīum Ateneo, 2017)
We attempted to model the Incubation Effect, a phenomenon in which a momentary break helps the generation of a solution to a problem, among students playing Physics Playground. We performed a logistic regression analysis to predict the outcome of the incubation using a genetic algorithm for feature selection. Out of 14 candidate features, those that significantly predicted the outcome were total badges earned prior to post-incubation, the problem’s level of difficulty, total attempts made prior to post-incubation, and time interval of post-incubation. We found evidence that incubation in the earlier part of the game is more beneficial than breaks at the later part where students may already be mentally exhausted.